The effect of perceived usefulness, perceived ease of use, and digital marketing on E - Wallet usage in marketplace ( case study Gen - Z Muslims in Yogyakarta ) - Nella Farah (Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga, 2023)
et,1/ad,c.1